ANALISIS PENGELOLAAN MODAL KERJA UNTUK MENILAI RETURN ON INVESTMENT (ROI) - Sarida Sirait; Sumaizar Sumaizar (Politeknik Bisnis Indonesia, 2021)
This research has a purpose, namely to know Working Capital Managementin terms of Return On Investment (ROI) at PT. Wahana Interfood Nusantara Tbk. The subjects in this study were PT. Wahana Interfood Nusantara Tbk and the object research on financial statements for the period 2019-2020 which includes items in Balance Sheet and Profit and Loss reports. Data collection method used in this research is documentation. The data analysis method used in This research is financial ratio analysis. Based on the research results, it is known that the performance of capital management working capital seen from (1) working capital turnover is categorized as less because it is below 6 times (2) cash turnover is good because it is above 10 times (3) receivables turnover it's good because it has reached above 7.2 times (4) inventory turnover is still categorized as less because it is below the industry standard which is 3.4 times. Performance The company's ROI is good because it is above the industry average standard which is 5.08 times. Keywords: Working Capital Management, Return On Investment